(3eOi EaGOI GdefGgL GddSGfjI GdMOjKI aj OQGSI GdfU GdbQBfj (B/s ((3GdOhMI (B- (3bWQ (B:s (3eDSSI hYj ddOQGSGJ hGdCHMGK ,s, 2022)
(3efP efJUa GdbQf GdYTQjf Edi jhefG gPG, SYi cKjQ ef GdHGMKjf Edi JhXja GdeOGQS hGdfXQjGJ hGdGJLGgGJ GddSGfjI hGdCOHjI aj eYGedI fUhU GdNWGH GdbQBfj, eeG CKGQ SDGdG Mhd eOi aGYdjI gPG GdEfJGL GdeYQaj GdMOjK djJhSd Hg Edi JMdjd GdfU GdESdGej hcTa eYGfjg hbO JfGhd gPG GdcJGH GdELGHI Ydi gPG GdJSGDd ef bHd fNHI ef GdYdeGA hGdHGMKjf ef RhGjG eNJdaI(B.s
(3HHdjhLQGajI (B: (3UaMI (B393-399.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3HdGZI GdbQBf GdcQjes